Spectroscopic Investigations of The Reaction Products of (NPH2)3 With Si(IV) - PAL SINGH, YOGENDRA; JADON, S.P.S. (Asian Journal of Chemistry, 2010)
Hexahydrocyclotriphosphazene, (NPH2)3 was used as a ligand and on refluxing 150-200 ºC in presence of benzene with SiCl4, the two reaction products, first mass aggregated, termed as Si(A) and on concentration of filtrate, product obtained, was termed as Si(B). On the basis of their 1H, 31P, NMR, UV and XRD spectral investigations, Si(A) and Si(B) have assigned the subsequently as (P3N3H4)5Si3Cl5 and (P3N3H4)5(SiCl2)4.